Effect of intravitreal bevacizumab on subfoveal choroidal thickness in eyes with diabetic macular edema - Haitham Y Al-Nashar (Delta Journal of Ophthalmology, 2016)
Purpose The purpose of this study was to evaluate the changes in subfoveal choroidal thickness (SFCT) in eyes with diabetic macular edema (DME) after intravitreal bevacizumab (IVB) injection. Patients and methods Thirty eyes diagnosed as nonproliferative diabetic retinopathy with DME were included in this prospective study. All eyes received an intravitreal injection of 1.25 mg/0.05 ml bevacizumab. Best-corrected visual acuity, SFCT, and central macular thickness were measured and recorded before the IVB injection and 1 month after the injection. The choroidal thickness was measured using enhanced depth imaging technique of Heidelberg Spectralis-optical coherence tomography. Results The mean age of the patients was 55.63±4.6 years, with a mean duration of diabetes of 8.26±1.96 years. The mean preinjection SFCT was 214.3±7.9 μm. The mean SFCT after 1 month of IVB injection was 215.5±6.8 μm, with no significant difference from the preinjection value (P=0.56). The mean change in the SFCT 1 month after intravitreal injection was 1.1±9.5 μm, with 0.5% change ratio. The correlation between change in SFCT and changes in central macular thickness and best-corrected visual acuity were 0.24 and −0.3, respectively, which were insignificant (P=0.2 and 0.09, respectively). Conclusion The IVB injection has no effect on the SFCT in eyes with DME.